ANDEH SETIA: Women's Economic Mobilizer in Sulit Air in Early 20th Century - Addi Arrahman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
Weaving handicrafts became the motor Minangkabau's economy at the beginning of the 20th. It encouraged the establishment of weaving centers, such as Amai Setia (1911) and Andeh Setia (1912). Amai Setia handicrafts' are still standing strong nowadays, while Andeh Setia is thus no longer known by the people of Sulit Air today. This paper uses the social history approach and exposes the history of the emergence and fall of Andeh Setia as an economic movement in Sulit Air. The establishment of Andeh Setia is inseparable from the role of ninik mamak and women in Sulit Air. Andeh Setia's success was ultimately drowned due to the loss of driving figures, the reduction in women's interest in weaving crafts, and the overflow of merantau. This finding also suggests that the economic independence of the people in Sulit Air, depends heavily on the role of perantau. This situation is thus an obstacle to the realization of economic independence. Kerajinan tenun menjadi penggerak perekonomian di Minangkabau pada awal ke-20. Ini mendorong terbentuknya pusat kerajaninan tenun, seperti Amai Setia (1911) dan Andeh Setia (1912). Kerajinan Amai Setia hingga saat ini masih dapat ditemukan, sedangkan Andeh Setia justeru tidak dikenal lagi oleh masyarakat Sulit Air hari ini. Padahal, pada tahun 1912, kualitas tenun Andeh Setia sangat diminati pasar. Itulah sebabnya, Andeh Setia menjadi penggerak ekonomi perempuan di Sulit Air. Artikel ini juga menemukan bahwa sebab hilangnya Andeh Setia adalah karena kehilangan tokoh penggerak, menurunnya minat kaum perempuan terhadap kerajinan tenun, dan menguatnya arus merantau.